Effects of Cisplatin in Neuroblastoma Rat Cells: Damage to Cellular Organelles - Giada Santin; Luigi Scietti; Paola Veneroni; Sergio Barni; Graziella Bernocchi; Maria Grazia Bottone (International Journal of Cell Biology)
Cisplatin (cisPt) is a chemotherapy agent used as a treatment for several types of cancer. The main cytotoxic effect of cisplatin is generally accepted to be DNA damage. Recently, the mechanism by which cisPt generates the cascade of events involved in the apoptotic process has been demonstrated. In particular it has been shown that some organelles are cisPt target and are involved in cell death. This paper aims to describe the morphological and functional changes of the Golgi apparatus and lysosomes during apoptosis induced in neuronal rat cells (B50) by cisplatin. The results obtained show that the cellular organelles are the target of cisPt, so their damage can induce cell death.